Delirious Mania in an Elderly, Challenges in Diagnosis and Treatment - Dhungel, Omkar; Shrestha, Najina; Sharma, Pawan; Pathak, Pankaj; Sapkota, Nidesh (Case Reports in Psychiatry, 2023)
Delirious mania is an acute neurobehavioral syndrome which can have the features of mania, delirium, psychosis and catatonia. There are no diagnostic and treatment guidelines of delirious mania which can lead to delayed treatment, increasing morbidity and mortality. The primary goal of this report is to raise awareness among healthcare professionals and improve patient outcomes for this potentially life-threatening condition. In this case report, we present an octogenarian female, a case of bipolar disorder, current episode manic, who had impaired orientation, delusion of persecution, and altered sleep–wake cycle. She was treated with a combination of mood stabilizer and antipsychotic and discharged after 24 days of admission.